A STUDY ON VISUAL CONTENT OF INFOGRAPHIC MEDIA HIERARCHY AS TEACHING MATERIAL ON BIOLOGY MATERIAL - Nuzul Syarbini; Elsi Susilawati; Nur Agilia Mardhatillah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
The development of technology makes learning media interesting to use and makes learning materials easier to understand. One form of interesting learning media is infographic media. Infographic media has become an effective teaching material in biology learning. Infographic media is closely related to the role of visual hierarchy. Visual hierarchy is an aspect that helps readers understand information in a structured and systematic manner. The method used in this research is exploratory descriptive. The researcher collected general information related to biology teaching materials and research studies from Biology Education students of UIN Alauddin Makassar who used infographic media as teaching materials. The analysis of visual literacy was based on the theory of visual hierarchy. In terms of visual hierarchy, three teaching material media have been implemented with a good visual hierarchy. The content, through a combination of colors, shapes or elements, an appropriate layout, and the selection of text models, creates contrast. This shows that a good understanding of visual hierarchy can produce infographics that are not only aesthetic but also comfortable for readers to read. Infographic teaching materials used for viral materials, the phylum Echinodermata, and the digestive system have followed an appropriate visual hierarchy as teaching material media. Of the three infographic media used as teaching materials, all have followed the principles of visual hierarchy.